Assessment of the role of ACC deaminase, IAA, and siderophore-producing bacteria isolated from Spratly Islands on the growth of Brassica juncea on the coral sand: ACC deaminase, IAA and siderophore-producing bacteria from roots and rhizosphere soil in Spratly Islands - Chi, Vu Thi Quynh; Hiep, Nguyen Viet; Hao, Le Thi My; Hai, Nguyen Quang; Anh, Do Thi Kim; Pham, Huong; Hau, Than Van; Viet, Nguyen Cong; Xinh, Ngo Thi; Loi, Nguyen Thi; et al. (Vietnam Journal of Science and Technology, 2023)
Root endophytic and rhizosphere bacteria play a significant role in enhancing plant tolerance and promoting growth by producing 1-aminocyclopropane-1-carboxylate (ACC) deaminase, indole-3-acetic acid (IAA), and siderophore. These bacteria have been isolated and screened from 45 plants’ roots and rhizosphere soil samples of 19 types of plants which are growing on 8 floating islands in Spratley Islands, Viet Nam. In which, 3 root endophytic bacteria strains were selected and identified to be Agrobacterium tumefaciens, Pseudomonas plecoglossicida, and Klebsiella aerogenes from roots of Scaevola taccada, Barringtonia asiatica (L.) Kurz, and Carica papaya, respectively. Correspondingly, 3 rhizosphere bacteria strains were selected and identified to be Bacillus velezensis, Bacillus aryabhattai, and Bacillus velezensis from rhizosphere soils of Canavalia maritima (Aubt) Thouars (C. obtusifolia DC.), Cucumis sativus, Heliotropium foertherianum, respectively. These strains were found could increase the germination rate of Brassica juncea’s seeds and 20-day-old fresh biomass, compared to the control treatment in the same condition of 10‰ saline watering. When these bacterial strains were combined as an inoculant, they indicated the same result on coral sand. Thus, the addition of selected endophytic and rhizosphere bacteria is efficient in improving the coral sand environment to enhance food crops’ development in the Spratly Islands.